The sensitivity level of landslide risk using Geographic Information System on the slopes of Mount Argopura, East Java, Indonesia - Basuki, Basuki; Sulistiawati, Nina; Verdian, Dimas; Naely, Zahrotun (Journal of Degraded and Mining Lands Management, 2023)
Jember is surrounded and limited by highlands such as Mount Argopura, Mount Ijen, Mount Argopura, and the southern karst mountains. In 2015-2022, the Jember area flooded during the rainy season and dried during the dry season. Changes in land cover that do not follow the science of soil preservation will cause disasters, including landslides and erosion. The purpose of this study is to assess the risk of landslides on the slopes of Mount Argopura through the Geographic Information System. The study used a field survey method that was divided into several stages, including making a working map, conducting a field survey, and analyzing the data in the laboratory. The sensitivity analysis of the landslide level used as the basis for the assessment used the relationship between the parameters of soil erodibility, soil erosion, slope and soil conservation, and slope length. The sensitivity of the level of landslide risk on Mount Argopura is divided into five classes, from very light to very heavy. The very light category covers 4.92% of the total area with erosion of 0.47 t/ha/year. The very heavy class covers 39.70% of the total area, with 1,360.79 t/ha/year erosion.